2013
DOI: 10.4085/1062-6050-48.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Muscle Strength After Anterior Cruciate Ligament Injury and Reconstruction

Abstract: Arbor. Dr Thomas is now with the Department of Kinesiology, University of Toledo, OH.Context: Quadriceps and hamstrings weakness occurs frequently after anterior cruciate ligament (ACL) injury and reconstruction. Evidence suggests that knee injury may precipitate hip and ankle muscle weakness, but few data support this contention after ACL injury and reconstruction.Objective: To determine if hip, knee, and ankle muscle weakness present after ACL injury and after rehabilitation for ACL reconstruction.Design: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 35 publications
2
90
0
2
Order By: Relevance
“…Gerber et al 42 noted that the quadriceps femoris muscle of the surgical limb could atrophy up to 30% just 3 weeks after ACLR, indicating the importance of resistive training immediately after surgery in an effort to mitigate atrophy and weakness. Other investigators 8,9 showed that at 6 months postoperatively, individuals can experience a loss of up to 50% of quadriceps strength relative to the contralateral limb and persistent limb weakness after returning to the previous activity level. Other evidence suggests that mitigating muscular atrophy may reduce the risk of rerupture, minimize patellofemoral pain, lessen mobility deficits, and return athletes to sport more quickly after ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerber et al 42 noted that the quadriceps femoris muscle of the surgical limb could atrophy up to 30% just 3 weeks after ACLR, indicating the importance of resistive training immediately after surgery in an effort to mitigate atrophy and weakness. Other investigators 8,9 showed that at 6 months postoperatively, individuals can experience a loss of up to 50% of quadriceps strength relative to the contralateral limb and persistent limb weakness after returning to the previous activity level. Other evidence suggests that mitigating muscular atrophy may reduce the risk of rerupture, minimize patellofemoral pain, lessen mobility deficits, and return athletes to sport more quickly after ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of this ligament and postoperative rehabilitation have been shown to be effective in restoring functional stability of the knee, 4 minimizing the development of osteoarthritis (OA), 5,6 and returning patients to their previous level of function. 5,7 However, persistent lower extremity muscle weakness, 8,9 insufficient dynamic knee stability, 10 and increased risk of posttraumatic arthrosis 3 have also been reported. A considerable number of individuals are unable to return to competitive sports despite successful rehabilitation or ACLR with rehabilitation.…”
mentioning
confidence: 99%
“…Despite these reports, clinically assessing and detecting quadriceps dysfunction during the terminal phases of rehabilitation remains difficult due to the often subtle reductions in strength and activation. 10,15 The importance of quadriceps function after ACLR cannot be overstated because reduced quadriceps function consistently has been related to long-term quadriceps weakness 10,14 and physical performance 3,16,17 and has been hypothesized to increase the risk for knee-joint osteoarthritis. 7 Assessment and comparison of range of motion and strength are common clinical tools used to track progress throughout the rehabilitation process.…”
mentioning
confidence: 99%
“…A number of observational studies (Konrath et al, 2016;Nomura et al, 2015;Takeda et al, 2006) have reported decrements in concentric (Tengman et al, 2014) and eccentric (Tengman et al, 2014;Thomas et al, 2013) knee flexor strength in the years following surgery as well as reduced muscle size (Nomura et al, 2015) and altered muscle architecture of the ST (Timmins et al, 2015). However, these studies are almost always constrained by small sample sizes, and several investigations have found conflicting results regarding the recovery of strength after rehabilitation (Aglietti et al, 1994;Ejerhed et al, 2003).…”
Section: Introductionmentioning
confidence: 95%